A Conceptual Model Depicting How Children Are Affected by Parental Cancer: A Constructivist Grounded Theory Approach - Elise S. Alexander; Georgia K. B. Halkett; Blake J. Lawrence; Moira O'Connor (MDPI AG, 2023)
Cancer patients' children are vulnerable to psychosocial and behavioural issues. The mechanisms underlying how children are affected by their parent's diagnosis are unknown, warranting further research. This study investigated how children are affected by their parent's cancer diagnosis and provides a theoretical model conceptualising this experience. Informed by methods of grounded theory, embedded within a social constructivist framework, 38 informants (15 health professionals (HPs); 11 parents; 12 children (5 to 17 years)) were interviewed using a semi-structured format. Three themes were identified: (i) children were worried and distressed because they felt alone, (ii) parents were unable to tend to children's needs because they were overwhelmed by practical factors, and (iii) HPs were not detecting children due to barriers that affected their visibility in clinical settings. The proposed Alexander's Children's Cancer Communication (ACCC) Model and clinical recommendations made can be used to guide the clinical practice and development of future intervention research.